Prevalence of BRAF V600E Mutation in the Iranian Patients with Hairy Cell Leukemia: A Retrospective Study - Karimi, Mojtaba; Monabbati, Ahmad; Sargazi Moghadam, Nasibeh (Asian Pacific Journal of Cancer Biology, 2021)
Objective: BRAF V600E mutation has several implications in hairy cell leukemia (HCL). The prevalence of This mutation has been investigated in various populations, but not in Iran. In this study, we evaluated the prevalence of BRAF V600E mutation in an Iranian HCL population as well as its association with the patients’ characteristics. Methods: In a retrospective (archival) study, 20 HCL patients with the confirmed immunophenotypic and morphologic diagnosis were included. Paraffin-embedded blocks of bone marrow aspirate were used to investigated BRAF V600E mutation using amplification refractory mutation system (ARMS) PCR. Demographic, clinical, laboratory, and immunophenotypic characteristics of patients were extracted from the patients medical profiles. Result: BRAF V600E mutation was present in 17 (85%) HCL patients and absent in three (15%) patients. The mean age of the patients was 44.76 ± 8.69 years in mutation-positive and 62.33 ± 8.69 in mutation-negative patients. This difference was statistically significant (p=0.013). No significant difference was found between the laboratory indices of the mutation-positive and mutation-negative groups. The clinical, morphologic, and immunophenotypic characteristics of the two groups were also statistically comparable. Conclusion: BRAF V600E mutation is present in the majority of the Iranian HCL patients and is associated with younger age of presentation.